Götterdämmerung for the Securities Act? - Joel Seligman (Washington University Law Quarterly, 1997)
A question suggested by a conference like this is whether the Securities Act of 1933 as a whole has reached a point of twilight or whether the inevitable proclivities of some issuers of securities to engage in fraud portends a greater longevity.
Keywords: Securities